Karl Polanyi. Remettre l'économie à sa place - Behrent, Michael C. (Sciences humaines, 2016)
History

Karl Polanyi and the Reality of Society - Behrent, Michael C. (History and Theory, 2016)
This essay reconsiders Karl Polanyi's famous thesis about the “embeddedness” of the economy through an examination of two recent books: For a New West, a collection of previously unavailable essays by Polanyi, and Fred Block and Margaret R. Somers's The Power of Market Fundamentalism: Karl Polanyi's Critique. The guiding thread of this analysis is the claim that a constant in Polanyi's thought was his belief in what he called “the reality of society,” that is, that society exists as a social fact over and above the individuals that constitute it. The essay begins by tracing Polanyi's intellectual development, drawing primarily on the essays found in For a New West. Polanyi's quest to reconcile individual freedom with social solidarity led him first, in the years between the First and Second World Wars, to embrace liberal socialism, before his readings in anthropology persuaded him that traditional economies “embed” the economy in social relations and that the nineteenth-century liberal project of a “disembedded” economy (through the so-called free market) is a departure from this anthropological norm. The essay then examines and questions Block and Somers's claim that Polanyi maintained that the economy is always “already embedded,” arguing notably that Polanyi believed that the advent of market society entailed an economy that was actually disembedded from social relations, not merely one that was re-embedded in an alternative set of institutions.
History
Keywords: already embedded; anthropology; capitalism; embeddedness; liberalism; markets; reality of society; socialism; society

Embedding Capital: Political-Economic History, the United States, and the World - Kramer, Paul A. (Journal of the Gilded Age & Progressive Era, 2016)
The article examines U.S. political and economical history in the context of its impact as well as influence to world affairs. Topics discussed include the Marxist's historical approaches to analysis of capital as in Karl Polanyi's take on American capitalism, "primitive accumulation" with regimes of commodification and the "new history of capitalism" hype. Also mentioned were transnational expansion of humanitarianism, international education sponsorship and Andrew Carnegie's philanthropy.
History
Keywords: United States - politics & government - history; capital; capitalism; economics - United States - history; embeddedness; humanitarianism

Karl Polanyi: A Life on the Left - Dale, Gareth (Columbia University Press, 2016)
Karl Polanyi (1886–1964) was one of the twentieth century's most original interpreters of the market economy. His penetrating analysis of globalization's disruptions and the Great Depression's underlying causes still serves as an effective counterargument to free market fundamentalism. This biography shows how the major personal and historical events of his life transformed him from a bourgeois radical into a Christian socialist but also informed his ambivalent stance on social democracy, communism, the New Deal, and the shifting intellectual scene of postwar America.The book begins with Polanyi's childhood in the Habsburg Empire and his involvement with the Great War and Hungary's postwar revolution. It connects Polanyi's idealistic radicalism to the political promise and intellectual ferment of Red Vienna and the horror of fascism. The narrative revisits Polanyi's oeuvre in English, German, and Hungarian, includes exhaustive research in five archives, and features interviews with Polanyi's daughter, students, and colleagues, clarifying the contradictory aspects of the thinker's work. These personal accounts also shed light on Polanyi's connections to scholars, Christians, atheists, journalists, hot and cold warriors, and socialists of all stripes. Karl Polanyi: A Life on the Left engages with Polanyi's biography as a reflection and condensation of extraordinary times. It highlights the historical ruptures, tensions, and upheavals that the thinker sought to capture and comprehend and, in telling his story, engages with the intellectual and political history of a turbulent epoch.
History
Keywords: European history; biography; history - Europe / Austria & Hungary; history - United States / 20th Century; history - modern; history - modern / 20th Century; social science; sociology

The Great Acceleration: An Environmental History of the Anthropocene since 1945 - McNeill, J. R. (Harvard University Press, 2016)
The pace of energy use, greenhouse gas emissions, and population growth has thrust the planet into a new age—the Anthropocene. Humans have altered the planet’s biogeochemical systems without consciously managing them. The Great Acceleration explains the causes, consequences, and uncertainties of this massive uncontrolled experiment.
History; Political Science
Keywords: anthropocene; history / modern / 20th Century; history / world; nature / environmental conservation & protection; political science / public policy / environmental policy

England's Great Transformation: Law, Labor, and the Industrial Revolution - Steinberg, Marc W. (University of Chicago Press, 2016)
With England’s Great Transformation, Marc W. Steinberg throws a wrench into our understanding of the English Industrial Revolution, largely revising the thesis at heart of Karl Polanyi’s landmark The Great Transformation. The conventional wisdom has been that in the nineteenth century, England quickly moved toward a modern labor market where workers were free to shift from employer to employer in response to market signals. Expanding on recent historical research, Steinberg finds to the contrary that labor contracts, centered on insidious master-servant laws, allowed employers and legal institutions to work in tandem to keep employees in line. Building his argument on three case studies—the Hanley pottery industry, Hull fisheries, and Redditch needlemakers—Steinberg employs both local and national analyses to emphasize the ways in which these master-servant laws allowed employers to use the criminal prosecutions of workers to maintain control of their labor force. Steinberg provides a fresh perspective on the dynamics of labor control and class power, integrating the complex pathways of Marxism, historical institutionalism, and feminism, and giving readers a subtle yet revelatory new understanding of workplace control and power during England’s Industrial Revolution.
History; Economics; Sociology
Keywords: business & economics / economic history; economic history; history / Europe / Great Britain; history / general; industrial revolution; social science / sociology / general

Polanyi'nin Modern İktisatın İnsan Anlayışına Eleştirileri - Akan, Seriyye (Polanyi's Criticisms on Modern Economics' Conception of the Human Being., 2016)
Discipline of economics, who already assimilated the mathematical and technical tools as a base for the expression of theory is almost lost its identity as a social science. This process has become visible through some historical breakups. These breakups have scientific, social and economic faces. While the developments in natural sciences had led the economists to imitate physics - since it uses more certain methods as a science; the market society which established after the industrial revolution separated humans from the economic understanding of the past eras. Rationality, which indeed a philosophical concept, purified from its philosophical context and integrated to economics. On the other hand, the mainstream economics which accepts the maximisation of interest as one of the components of human nature prevailed the economics literature. The modern economics' conception of human had shaped via the steps which we briefly mentioned above. Karl Polanyi (1886-1964) had criticized the human conception of modern economics by using social anthropological methods. He had claimed that market system did not emerged spontaneously, the nature of human did not change throughout history, and primitive economics was totally different from today's market society since the economic relations were embedded in the other social relations. In this article, we tried to analyse Polanyi's criticisms on modern economics' human conception. For this reason, we firstly argued the term rationality in the economic context, since it would be a basis for our subject. Then we emphasized the thesis of "uncahged nature of human" which highlighted by Polanyi, discussions on primitive economies, and the market society which established parallel to the industrial revolution respectively. (English)
History; Anthropology
Keywords: holism; market society; primitive economies; rationality; social anthropology